Climate Change: Impacts on Sustainable Development Goals and Human Rights - Shahid, Fakhara; Ahmad, Adil (Annals of Human and Social Sciences, 2023)
Climate change has sharpened many social, economic and political diseases faced by global community. Climate change has become a threat multiplier, disproportionately effecting the marginalized communities and posing serious threats to fundamental human rights. The interconnectedness of climate change with human rights and SDGs needs a multidimensional and multilevel approach at local, national, and international level. The topic of this interconnectedness has become the concern of academic as well as of policy making circles. This article emphasizes on the urgent need to meet with this multidimensional challenge by using an interdisciplinary and longitudinal qualitative research method. The results of the study have shown that the global sustainable development goals cannot be achieved by international world until before tackling the climate change. An integrated policy framework, capacity building, global collaboration, community engagement, and investment in renewable energy resources is dire need of time in order to safe the basic human rights on the planet earth.